Investigation of bookal epithely in various pathological states: review of literature - Savitskiy, I.; Magdenko, A.; Orel, K.; Mizevich, Y.; Dvoretsky, R. (Journal of Education, Health and Sport, 2017)
The work analyzes the scientific works of foreign and domestic scientists over the past 10 years, devoted to the study of buccal epithelium in various pathological conditions. It has been established that the BE study is becoming more popular because it is non-invasive, painless and highly informative, and is characterized by the convenience of collecting the material. Currently, there are two main areas of research: the first is based on the study of changes in intracellular microelectrophoresis and electrokinetic activity of cells of the BE; The second - on the selection and study of markers in the dynamics, specific for specific diseases. Both directions can be promising for the diagnosis of various pathological conditions of organs and systems.